Clinical Outcomes and Plasma Concentrations of Baloxavir Marboxil and Favipiravir in COVID-19 Patients: An Exploratory Randomized, Controlled Trial - Lou, Yan; Liu, Lin; Yao, Hangping; Hu, Xingjiang; Su, Junwei; Xu, Kaijin; Luo, Rui; Yang, Xi; He, Lingjuan; Lu, Xiaoyang; Zhao, Qingwei; Liang, Tingbo; et al. (European journal of pharmaceutical sciences, 2021)
•An exploratory randomized, controlled trial of baloxavir marboxil and favipiravir in COVID-19 patients were conducted.•The free drug concentrations of baloxavir acid and favipiravir are generally lower than their respective EC50 values.•Add-on either baloxavir or favipiravir to the current standard treatment resulted in no additional antiviral benefit. Background: Effective antiviral drugs for COVID-19 are still lacking. This study aims to evaluate the clinical outcomes and plasma concentrations of baloxavir acid and favipiravir in COVID-19 patients. Methods: Favipiravir and baloxavir acid were evaluated for their antiviral activity against SARS-CoV-2 in vitro before the trial initiation. We conducted an exploratory trial with 3 arms involving hospitalized adult patients with COVID-19. Patients were randomized assigned in a 1:1:1 ratio into baloxavir marboxil group, favipiravir group, and control group. The primary outcome was the percentage of subjects with viral negative by Day 14 and the time from randomization to clinical improvement. Virus load reduction, blood drug concentration and clinical presentation were also observed. The trial was registered with Chinese Clinical Trial Registry (ChiCTR 2000029544). Results: Baloxavir acid showed antiviral activity in vitro with the half-maximal effective concentration (EC50) of 5.48 μM comparable to arbidol and lopinavir, but favipiravir didn't demonstrate significant antiviral activity up to 100 μM. Thirty patients were enrolled. The percentage of patients who turned viral negative after 14-day treatment was 70%, 77%, and 100% in the baloxavir marboxil, favipiravir, and control group respectively, with the medians of time from randomization to clinical improvement was 14, 14 and 15 days, respectively. One reason for the lack of virological effect and clinical benefits may be due to insufficient concentrations of these drugs relative to their antiviral activities. One of the limitations of this study is the time from symptom onset to randomization, especially in the baloxavir marboxil and control groups, which is higher than the favipiravir group. Conclusions: Our findings could not prove a benefit of addition of either baloxavir marboxil or favipiravir under the trial dosages to the existing standard treatment. [Display omitted]